POMEGRANATE ATTENUATES ACUTE GENTAMICIN-INDUCED NEPHROTOXICITY IN SPRAGUE-DAWLEY RATS: THE POTENTIAL ANTIOXIDANT AND ANTI-INFLAMMATORY EFFECTS - AL-KURAISHY, HAYDER M; AL-GAREEB, ALI I; SADEK AL-NAIMI, MARWA SALIH (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Nephrotoxicity is a renal-specific situation in which the excretion of toxic metabolites is reduced due to toxic agents and drugs. Gentamicin is an antibiotic belongs to aminoglycoside group which may induce nephrotoxicity due to induction of oxidative stress. Pomegranate is a component of the traditional medicine called Punica granatum with significant nephron-protective effect. Therefore, the objective of the present study was to evaluate the nephronprotective effect of pomegranate in gentamicin-induced nephrotoxicity. Methods: A total of 30 male Sprague-Dawley rats were used which divided into Group 1 (n=10): Rats treated with distilled water 5 ml/kg plus normal saline 5 ml/kg for 12 days, Group 2 (n=10): Rats treated with distilled water 5 ml/kg plus gentamicin 100 mg/kg for 12 days, and Group 3 (n=10): Rats treated with pomegranate 100 mg/kg plus gentamicin 100 mg/kg for 12 days. Blood urea, serum creatinine, malondialdehyde (MDA), kidney injury molecule (KIM-1), and cystatin-C were measured in both control and experimental groups. Results: Rats treated with gentamicin showed nephrotoxicity as evident by significant elevation in serum creatinine, blood urea, serum creatinine, KIM-1, MDA, and cystatin-C sera levels. Pomegranate leads to significant reduction of blood urea and serum creatinine compared to gentamicin group, p<0.05. Pomegranate also reduced MDA, KIM-1, and cystatin-C sera levels significantly compared to gentamicin group, p<0.01. Conclusion: Pomegranate produced significant nephroprotective effect on gentamicin-induced nephrotoxicity through modulation of oxidative stress and inflammatory biomarkers.